VD_FINDINFO HC / 2012 / 741 vom 16. November 2012 - VD Tribunal cantonal (2012)
BAIL À LOYER, DEMEURE DU DÉBITEUR, LOYER, RÉSILIATION IMMÉDIATE | 257d CO, 308 CPC (CH), 310 CPC (CH), 312 al. 1 CPC (CH), 315 al. 1 CPC (CH)